The Influence Of Digital Technology Use On The Sustainability Of Msme Businesses In Bandung City - Rafi, Rafi Iskandar Putra; Pramanik, Nuniek Dewi (JAKI : Jurnal Akuntansi, 2025)
This study aims to measure the extent of the influence of the Utilization of Digital Technology (X) on the Sustainability of MSME Businesses (Y). In this research process, a quantitative method was applied with a random sampling technique, namely random sampling where each individual in the population has an equal chance of being selected. The results of this study show a stimulant influence on variable X on variable Y, with the results of data processed using SPSS 30 amounting to 93.5% while the remaining 6.5% comes from other factors outside the scope of this study and is not subject to further analysis. Although this shows the significant use of digital technology on the sustainability of MSME businesses, there are also other external factors that must be considered again in further research which will later obtain a more comprehensive picture of the sustainability of MSME businesses.